Representasi Matematis Siswa Kelas VIII pada Materi Segiempat Ditinjau dari Gaya Belajar Honey Mumford Tipe Aktivis - Utama, Alfian Eka; Oktavihari, Dita (Griya Journal of Mathematics Education and Application, 2025)
Mathematical representation ability is one of the essential and fundamental components that students need to express their mathematical ideas during the learning process. However, field observations show that students' ability to represent mathematical ideas is still relatively low, including those related to the topic of quadrilaterals. This condition is influenced by the diversity in students’ learning processes, one of which is caused by differences in learning styles. To investigate this issue, a study is needed to obtain a comprehensive description of students' forms of mathematical representation in solving quadrilateral problems, viewed from the perspective of their learning styles. The learning style used in this study is Honey and Mumford's learning style model. This study employed a qualitative approach with a phenomenological design. The subjects of the study were three eighth-grade students from MTsN in Mataram City. The data collection techniques used in this study were questionnaires, tests, and interviews. The results showed that students with an activist learning style tend to experience difficulties in modeling their ideas geometrically when solving problems related to quadrilaterals. They were less able to model and interpret problems in detail. However, when faced with problems that involved representing their ideas to find solutions to real-life situations, in general, students with an activist learning style were able to find appropriate solutions.